Kredit: Suatu Kajian Perspektif Hukum Islam - Muhibbuddin Muhibbuddin (Lembaga Penelitian dan Pengabdian Kepada Masyarakat Institut Agama Islam Negeri Sultan Amai Gorontalo, 2017)
This study aims to examine the legal status of credit sale and purchase. This phenomenon is inseparable from the context of Islamic legal thinking about the legal status of the credit financing system with the addition of prices. Buying and selling credibility is one alternative for consumers to own the goods they want. The results of the study showed that there were three views of scholars regarding the legal status of the credit system sale and purchase, namely: a view that absolutely forbids, can be absolutely, and tafshil (between neutral and forbidden). The author argues that the issue of buying and selling credit is something that is not mentioned in the Qur'an, so that this authority is returned to the community, as long as it does not violate the Islamic business ethics, and there is mutual willingness to conduct transactions. Moreover, buying and selling credit is a bigger problem.